Analisa Kualitas Pelayanan dengan Pendekatan Service Quality dan Quality Function Deployment (Studi Kasus: Bagian PSA (Pelayanan Satu Atap di ITATS) - Amahala, Ainur Rahmania Dj; Suparto, Suparto (CV. Kalimasada Group, 2024)
Higher education becomes not only the center of knowledge but also a place to explore and improve all aspects of excellent service that can improve its image. Therefore, every university will be increasingly required to always provide good service because students are always looking for the one that provides the best service for them. Institut Teknologi Adhi Tama Surabaya, or ITATS, is the most complete and qualified engineering college in East Java. However, there are still deficiencies in service quality that need to be improved, such as the quality of service for new student registration. The registration service at ITATS is still quite complicated, inefficient, and ineffective. This study aimed to determine the attributes of service quality and improve service performance in the future. It employed the service quality (servqual) and quality function deployment (QFD) methods. The results of the ITATS service quality research indicated that the biggest gap was in the assurance dimension, with a value of -0.39. Meanwhile, theemployee was the attribute with the highest level of importance that could provideservices effectively and efficiently